ANALISIS PERBANDINGAN KETEPATAN PREDIKSI KEBANGKRUTAN ANTARA ALTMAN DAN MODEL SPRING GATE DI PERUSAHAAN YANG DELISTING DI BEI - Dasriyan Saputra; Fazria Nur Daluh Arisyah (Jurnal GeoEkonomi, 2024)
The aim of this research is to analyze significant non-uniformities in the bankruptcy prediction process through the use of the Altman Z score, and which bankruptcy prediction model is most suitable for predicting business failure. In this research, the data used comes from company financial reports available on the Indonesia Stock Exchange website. The focus of this research is on companies that have experienced delisting and have been listed on the Indonesia Stock Exchange during the 2019-2021 period. To identify comparisons between the six listed companies, data analysis will involve the application of non-parametric statistical testing techniques. namely the Wilcoxon Signature Rating Test using SPSS and Accuracy and Error Checking using Microsoft Excel. The findings from this research show that there is a significant difference between the Altman Z score and the Springate S score in their ability to predict the possibility of bankruptcy. The findings show that a more effective model in predicting bankruptcy is using the Altman Z score.